2016
DOI: 10.1159/000444007
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Gradient and Clinical Outcome in Patients Undergoing Transcatheter Aortic Valve Implantation for Severe Aortic Stenosis

Abstract: Objectives: To explore the relation between the baseline aortic valve gradient (AVG) as a continuous variable and clinical outcomes following transcatheter aortic valve implantation (TAVI) in general and specifically in patients with high-gradient aortic stenosis (AS). Methods: We reviewed 317 consecutive patients who underwent TAVI at our institution. We investigated the relation between AVG as a continuous/categorical variable and outcome among all patients and in patients without low-flow low-gradient AS, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Le Ven et al found that a decrease in AVG level was not associated with a significant increase in mortality after adjustment for multiple clinical variables among 639 severe AS patients (adjusted HR = 1.05, 95% CI 0.95–1.17, per 10 mm Hg decrease in mean AVG, P = 0.33) . Witberg et al analyzing data from one institution ( n = 317) reported an overall inverse association between AVG and post‐TAVR mortality (HR = 0.82, P = 0.003 per 10 mm Hg increase in mean AVG) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Le Ven et al found that a decrease in AVG level was not associated with a significant increase in mortality after adjustment for multiple clinical variables among 639 severe AS patients (adjusted HR = 1.05, 95% CI 0.95–1.17, per 10 mm Hg decrease in mean AVG, P = 0.33) . Witberg et al analyzing data from one institution ( n = 317) reported an overall inverse association between AVG and post‐TAVR mortality (HR = 0.82, P = 0.003 per 10 mm Hg increase in mean AVG) .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few trials evaluated the relationship between AVG as a continuous variable and mortality. Kodali et al investigated predictors of mortality post‐TAVR among 348 patients with severe AS, and found that every 10 mm Hg increment in mean AVG was associated with an adjusted 18% reduction in 2‐year mortality ( P = 0.003) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations